2021
DOI: 10.1021/acs.jpcb.0c11057
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Properties in Disordered Condensates

Abstract: Biomolecular condensates appear throughout the cell serving a wide variety of functions. Many condensates appear to form by the assembly of multivalent molecules, which produce phase-separated networks with liquidlike properties. These networks then recruit client molecules, with the total composition providing functionality. Here we use a model system of poly-SUMO and poly-SIM proteins to understand client−network interactions and find that the structure of the network plays a strong role in defining client r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Sequence also influences the network structure of the dense phase, where most sequences form few correlated bonds but a small subset (such as ℓ = 1 and ℓ = 12) form longer aligned segments. It has recently been shown that such aligned “zippers” can tune functional properties such as client recruitment [ 38 ], providing another link between sequence and function.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence also influences the network structure of the dense phase, where most sequences form few correlated bonds but a small subset (such as ℓ = 1 and ℓ = 12) form longer aligned segments. It has recently been shown that such aligned “zippers” can tune functional properties such as client recruitment [ 38 ], providing another link between sequence and function.…”
Section: Discussionmentioning
confidence: 99%
“…With Ub 5 and SUMO2 7 probes in hand, we turned our attention for simultaneous live cell delivery. We used low micromolar concentration of these probes to avoid substantial effects on the endogenous Ub and SUMO2 concentrations, which are estimated to be in ∼80‐100 micromolar range [30,31] . We mixed probes Ub 5 and SUMO2 7 with the commercial enhanced green fluorescent protein (EGFP) in PBS, containing the non‐ionic surfactant pluronic™ F‐68.…”
Section: Resultsmentioning
confidence: 99%
“…We used low micromolar concentration of these probes to avoid substantial effects on the endogenous Ub and SUMO2 concentrations, which are estimated to be in ~80-100 micromolar range. [30,31] We mixed probes Ub 5 and SUMO2 7 with the commercial enhanced green fluorescent protein (EGFP) in PBS, containing the non-ionic surfactant pluronic™ F-68. We included EGFP to test the efficacy of MBL with larger proteins and to compare its distribution to Ub and SUMO2.…”
Section: Live Cell Protein Deliverymentioning
confidence: 99%
“…29 Empirically classifying biomolecular condensates on a spectrum from fluid (healthy) to rigid (disease) motivates us to learn how their material properties arise from their constituent IDPs. 39–41 But although an enormous amount of experimental data is accessible in online databases, 42–44 via web-based interfaces (), 45 there is no mechanistic understanding of how IDP molecular architecture controls the structure of their dense phase.…”
Section: Introductionmentioning
confidence: 99%